(untitled) (International Journal of Creative Future and Heritage (TENIAT), 2014)
Abstrak Kreativiti dalam proses pembuatan alat muzik merangkumi aspek daya imaginasi dari pemikiran asal, ekspresi seni dan budaya, sensitif kepada nilai estetik dan pemerhatian kontekstual. Kepentingan elemenelemen ini menyumbang kepada struktur pembuatan alat muzik yang dapat diterima berdasarkan nilai kualiti estetik dan kepentingan filosofikal selain dari keperluan nilai komersil. Dalam pasaran komersil, kajian ini telah merumuskan bahawa ketiadaan produk instrument muzik buatan tempatan memerlukan tindakan susulan dari institusi dan organisasi yang berkaitan. Tulisan ini juga mengupas aktiviti kreatif pembuatan alat muzik yang dapat dijadikan wahana untuk mempromosi dan mengarusperdanakan industri muzik dalam penjanaan ekonomi kreatif Negara. Abstract Creativity in music instrument making involves the notion of ‘imagination’ from original thoughts, expression of the art and culture, aesthetic sensitivity and contextual awareness. These are vital elements of associations contributing to the structure of music instrument making which can be perceived not just through its commercial preferences but also through its aesthetic qualities or philosophical significance. Along the commercial lines, findings have concluded that the absence of ‘local-made’ music instrument products in Malaysian music outlets, which consequently highly dependable on imported products, are an insights to be addressed by both related institutions and relevant authorities. This paper too explore some inspiring creative activities in the cottage industry of music instrument making that serves to propagate and to promote the music industry as a distinctive opportunity and avenue in generating the nation’s creative economy